Strategic Sequences in Fat Graft Survival. Issue 3 (March 2015) - Guo, Jimmy; Widgerow, Alan D.; Banyard, Derek; Toranto, Jason; Wirth, Garrett A.; Paydar, Keyianoosh; Tocco-Tussardi, Ilaria; Evans, Gregory R.D.
Abstract : Abstract: Although lipotransfer, or fat grafting, is a commonly used procedure in aesthetic and reconstructive surgery, there is still variability in graft survival and neoadipogenesis from one procedure to the next. A better understanding of the sequential molecular events occurring with grafting would allow us to strategize methods to improve the regenerative potency of the grafted tissue. These steps begin with an autophagic process, followed by the inclusion of stromal vascular fraction and matrix components. By tailoring and modifying each of these steps for a particular type of aesthetic or reconstructive procedure, strategic sequencing represents a dynamic approach to lipotransfer with the aim of maximizing adipocyte viability and growth. In the implementation of the strategic sequence, it remains important to consider the clinical viability of each step and its compliance with the US Food and Drug Administration regulations. This review highlights the basic science behind clinically translatable approaches to supplementing various fat grafting procedures.